Heat resistance of graphitized steel - Savchenko, V. O. (Science and Transport Progress, 2014)
Purpose. The investigation of temperature dependences of steels' mechanical properties and heat resistance under conditions of thermal cyclic loads. It's necessary to determine the mechanical properties and heat resistance indices of graphitized steels and cast iron VCh400 within the temperature range of 20…800°С. Methodology. Graphitized steels of the following chemical composition (mass %): 0.61…1.04C; 1.19…1.59%Si; 0.32…0.37%Mn; 0.12…0.17%Al; 0.008…0.014%S and 0.016…0.025%Р have been heat-treated according to the mode: heating up to 810°С – holding for 2 hours; cooling down to 680°С – holding for 2 hours with further cooling using the furnace in order to provide the ferrite-pearlite metallic base with graphite inclusions. In order to determine heat resistance indices (heat stresses index K and the material's resistance criterion at thermal cyclic load C) the indices of graphitized steels' and cast irons' mechanical properties in the temperature range of 20…800°С have been investigated. Findings. It has been established that as a result of lower carbon content and smaller quantity of graphite inclusions, graphitized steel exceeds such indices of nodular cast iron VCh400 as: tensile strength and plasticity at room and high temperatures, and also heat resistance criteria K and C. This steel can be used to manufacture articles operating under conditions of thermal cyclic loads. Originality. Tensile strength and percent elongation of graphitized steels within the temperature range of 20…800°С have been determined. Calculations of heat resistance criteria to the heat stresses index K and the material's resistance criterion at thermal cyclic loads C within the temperature range 20…800°С in comparison with nodular cast iron of VCh400 grade have been carried out. Practical value. The expediency of using graphitized steel for manufacturing of articles operating under conditions of thermal cyclic loads has been shown.